Stock Returns and Cost Efficiency of Listed Commercial Banks in China – A Stochastic Frontier Analysis - TAO, Hongyi (2018)
This study examines the determinants of bank efficiency of 25 listed Chinese commercial banks over the period of 2011-2017. A two-stage Stochastic Frontier Analysis (SFA) is used to estimate the cost efficiency. Based on the evaluation of determinants of cost efficiency, this paper tries to combine stock returns with bank efficiency and discuss the relationship between them. The results indicate that macroeconomic condition, capital adequacy, economies of scale, liquidity has positive relationship with cost efficiency, while bank profitability might be negatively related to cost efficiency. Although it confirms the positive correlation between the operating efficiency of commercial banks and stock returns, the degree of influence of bank operating efficiency on stock returns is very limited. There is still room for further improvement in the efficiency level of listed commercial banks in China. The efficiency difference between state-owned commercial banks and joint-stock commercial banks is narrowing. The operating efficiency of commercial banks has a significant impact on their performance in the stock market.